Adaptation Strategies of PT. Gajah Tunggal Tbk in Implementing CSR Programs During the COVID-19 Pandemic (2020-2022) - Faskan Aditama; Triyanti Anugrahini (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
Gajah Tunggal Tbk, as the largest tire manufacturer in Southeast Asia, is one of the manufacturing companies that has survived during the Covid-19 pandemic. PT. Gajah Tunggal Tbk actively participates in CSR practices based on the Four Pillars: Environmental, Welfare, Community, and Economic. The focus of this research is to describe and analyze adaptation strategies in the implementation of Gajah Tunggal's CSR program during the Covid-19 pandemic. This research approach utilizes qualitative methods with descriptive research types. Data collection involves in-depth interviews and document studies on the annual reports and sustainability reports of PT. Gajah Tunggal Tbk (2021-2022). The research results indicate that adaptation strategies in the implementation of Gajah Tunggal's CSR program are carried out by following national policy instructions through the application of Covid-19 protocols and handling, determining CSR program initiatives based on mapping and formulation results agreed upon by stakeholders, and implementing CSR programs during the Covid-19 pandemic (2020-2022).